TATA GUNA LAHAN DAN BANJIR DI KOTA TOLITOLI SULAWESI TENGAH - I Made Adhika (Environmental Research Center (PPLH) of Udayana University, 2012)
Tolitoli located in the lowlands between the bays and hills. When rainfall occurs in the hills and tides occurs in the bay, the City will be flooded. Flood level depends on rainfall that occurred. In the year 2009 and 2010 a big flood happenend in the city. The aims of this paper are to discuss the relationship between land use and urban environment in flooding context. To achieve these goals are performed field observation, tracing a map of the area, interviews with leaders and Tolitoli's people. From the results observation will be described, interpreted, and narrated. The study result shows the land use in upland and city area, the physical condition of the city, and social culture have a significant role that cause a flooding in the study area.